Investigation of the final stages of solidification and eutectic phase formation in Re and Ru containing nickel-base superalloys - Heckl, Astrid; Rettig, Ralf; Cenanovic, S.; Göken, Mathias; Singer, Robert (Journal of Crystal Growth, 2010)
The microstructure resulting from the final stages of solidification-commonly referred to as eutectic islands-has been analysed in detail for three nickel-base superalloys containing Re and Ru. Focused ion beam 3-D reconstruction and EBSD-analysis were used to clarify the origin of different eutectic structure types. One common type of parent 3-D eutectic structure was identified. The solidification process of the final solidifying liquid has been further investigated by electron probe microanalysis mappings along with DICTRA simulations. Two models for diffusion controlled phase transformations are shown to present a fair description of the solidification sequence. (C) 2010 Elsevier B.V. All rights reserve
Keywords: Final stage solidification; Microsegregation; 3-D microstructure; Eutectic island; FIB tomography; Nickel-base superalloys